Performance of crossbred cattle and comparison of sires evaluation methods under organized farm condition - SAHANA, G; GURNANAI, M (The Indian Journal of Animal Sciences, 2013)
The efficiency of sire evaluation methods in organized head with small progeny group size was examined along with performance evaluation of crossbred cattle. The data on 1 224 first lactation performance records of Karan Fries (Holstein Freisian x zedu) cows born out of 129 sires and spread over 21 years were used to examine the efficiency, accurcy and repeaatability of 5 sire evaluation methods, Viz. simple daughter average index (I), contemporary comparison method (CC), least squares method (LSQ), simplified regressed least squares method (SRLS) and best linear unbiased prediction (BLUP). The least squares of variance showed that genetic group had highly significant (P